Peningkatan Kapasitas Penyisipan Audio Data Hiding Berbasiskan Modifikasi Metode Least Significant Digit - Tegar Palyus Fiqar; Tohari Ahmad (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Nowadays, the needs of data security is proportional to the amount of data usage as the effect from easiness in internet access. There are many ways to protect data in order to avoid data leakage, such as cryptography, watermarking, and data hiding. The latter is conducted by hiding secret data into a carrier. A popular method in data hiding is Least significant digit (LSD). The hiding is carried out by changing the value of binary secret data into decimal in specific segment. Then, the decimal value of secret data is inserted into the carrier. The process in LSD method is relatively simple and easier to implement, but the LSD has weakness in pivoting point as reference of data changes. This results in a change into the original data carrier. Additionally, this also has limited amount of data capacity that can be inserted.On the other hand, Global-Section Search method (GSS) is an optimization method used to find an optimum value between two signals. Newly acquired signal GSS is further used as a pivoting point and slot area to paste the data secret.This study proposes a new method of data hiding by using Least Significant Digit and Global-section search (LSD-GSS) to increase the capacity of secret data insertion. The performance of LSD-GSS as proposed method is tested by comparing the LSD method and using 15 data sets of audio in various genres as carrier media and various large capacity of 12 secret data. SNR is used to find out the quality of hidden data audio. The experimental result shows that the LSD-GSS has increased the capacity of secret data that can be inserted without changing the original data carrier.